Application of Remote Sensing in Training Geospatial Cognitive Abilities of Secondary Students - Wu, Li; Liu, H. Y.; Peng, P. (International Journal of Online and Biomedical Engineering (iJOE), 2014)
The formation and development of geospatial cognitive abilities are an important aspect of training geographic literacy of secondary students, because these abilities have vital significance for solving their own problems related to geography and its study. However, training geospatial cognitive abilities is currently quite weak in our secondary school’s geography curriculum. Many secondary students now have low geospatial cognitive abilities. Remote sensing has a lot of advantages over other training in geospatial cognitive abilities. Therefore, how to use remote sensing in training geospatial cognitive abilities of secondary students should be given necessary importance. Based on the partition of essential factors of geospatial cognitive abilities, this study analyzed some advantages and summarized five teaching strategies integrating remote sensing in training geospatial cognitive abilities in our secondary education, which can provide applicable opinions and suggestions for developing geospatial cognitive abilities of secondary students.